Report of the 37th general assembly - ASEAN Inter-parliamentary organization - Asean Inter- parliamentary assembly, Hội đồng liên nghị viện ASEAN (ASEAN Inter - Parliamentary Assembly (AIPA), 2016)
Hội nghị lần thứ 37 của tổ chức liên nghị viện ASEAN được tổ chức tại Myanmar từ ngày 29/9 đến ngày 3/10 năm 2016.